Glycemic response to SSBs and ASBs: the role of mixed meals and individual variability - Sejin Kim; YoonJu Song (Nutrition Journal)
Abstract Background While artificially sweetened beverages (ASBs) are widely reported to have minimal glycemic impact compared to sugar-sweetened beverages (SSBs), their effects in mixed meal conditions and individual variability in response remain poorly understood. This study aimed to evaluate postprandial glycemic response (PPGR) and individual variability in response to an SSB (regular cola) and an ASB (zero cola), both in single and mixed conditions, using continuous glucose monitoring (CGM). Methods A total of 66 healthy young adults participated in this 14-day, non-randomized crossover intervention study. Test meals included 75 g oral glucose load as a reference, muffin, regular cola, zero cola, muffin with regular cola (MRC), and muffin with zero cola (MZC). PPGR was evaluated using incremental area under the curve. The glucose dip was assessed as the minimum glucose reduction from baseline. Participants were classified as MZC-High (n = 17) if their glycemic response to MZC was higher than to MRC, and as MZC-Stable (n = 44) if MRC showed the higher response. Results The 75 g oral glucose load reference exhibited a typical glycemic pattern, peaking at 45 min before steadily declining. The muffin induced a moderate glycemic response, while regular cola led to a rapid glucose rise followed by a sharp decline. When combined with a muffin, MRC exhibited a slightly higher glycemic response (iAUC180:161.6 mmol∙min/L), whereas MZC showed a similar response to the muffin alone (113.3 and 111.1 mmol∙min /L, respectively). At 120 min, the glucose dip was most pronounced for regular cola, whereas oral glucose load and muffin showed smaller reductions. These patterns persisted at 180 min, with oral glucose load showing the largest drop. Mixed meals attenuated glucose dips, with MRC and MZC preventing excessive declines. Individual responses analysis revealed that while the overall iAUC was not significantly different between muffin alone and MZC, 26 participants (MZC-High Responders) exhibited a higher iAUC with MZC than with MRC, suggesting variability in glucose regulation. Comparisons between MZC-High Responders and MZC-Stable participants showed no significant differences in age or body composition. Conclusion While zero cola alone or in combination with a muffin had a minimal overall glycemic impact, some individuals exhibited higher glycemic responses in mixed conditions. These findings suggest that individual variability and mixed condition should be considered when consuming artificially sweetened beverages. Trial registration Clinical Research Information Service (CRIS, cris.nih.go.kr) No. KCT0009921.